Investigation of acute toxicity of novel 3,7-dihydro-1H-purine-2,6-dione derivatives - Veretenina, A. A.; Vasylyev, D. A.; Веретеніна, Ася Анатоліївна; Васильєв, Денис Андрійович (EEA, INDIA, 2021)
The past thirty years of investigation and development in pharmacophore design has produced revolutionary results. Ring structure give molecules their basic form, determine whether molecules are rigid or flexible, and keep substituents in their appropriate sites. In many biologically active structures, rings are directly involved in communications with cell receptors, either through heteroatoms forming hydrogen bonds with suitable protein residues or through hydrophobic interactions. The latter relays to many branches of bioinformatics like in-silico algorithms, biochemical assays, better pharmacokinetics/pharmacodynamics (PK/PD) models, ADME models, and wide variety of toxicology surveys.
Keywords: xanthine; purine; synthesis; acute; toxicity